Effect of setmelanotide, a melanocortin‐4 receptor agonist, on obesity in Bardet‐Biedl syndrome - Haws, Robert (Diabetes Obes Metab, 2020)
AIM: To report an analysis of ~1 year of setmelanotide treatment for obesity and hunger, as well as metabolic and cardiac outcomes, in individuals with Bardet‐Biedl syndrome (BBS). MATERIALS AND METHODS: Individuals aged 12 years and older with BBS received once‐daily setmelanotide. The dose was titrated every 2 weeks to establish the individual therapeutic dose (≤3 mg); treatment continued for an additional 10 weeks. Participants who lost 5 kg or more (or ≥5% of body weight if <100 kg at baseline) continued into the 52‐week extension phase. The primary outcome was mean percent change from baseline in body weight at 3 months. Hunger scores and safety were secondary outcomes. RESULTS: From February 2017 and February 2018, 10 individuals were screened; eight completed the 3‐month treatment phase and seven completed the extension phase. Mean percent change in body weight from baseline to 3 months was −5.5% (90% CI, −9.3% to −1.6%; n = 8); change from baseline was −11.3% (90% CI, −15.5% to −7.0%; n = 8) at 6 months and −16.3% (90% CI, −19.9% to −12.8%; n = 7) at 12 months. All participants reported at least one treatment‐emergent adverse event (AE), most commonly injection‐site reaction. No AEs led to study withdrawal or death. Most, morning, and average hunger scores were reduced across time points. CONCLUSIONS: Setmelanotide reduced body weight and hunger in individuals with BBS and had a safety profile consistent with previous reports. Setmelanotide may be a treatment option in individuals with BBS‐associated obesity and hyperphagia.